2021
DOI: 10.2147/opth.s321371
|View full text |Cite
|
Sign up to set email alerts
|

Combined Pars Plana Vitrectomy and Segmental Scleral Buckle for Rhegmatogenous Retinal Detachment with Inferior Retinal Breaks

Abstract: Purpose To describe a variation of the traditional segmental scleral buckle (SB) without an encircling band combined with 23-gauge pars plana vitrectomy (PPV) for the management of rhegmatogenous retinal detachment (RRD) with inferior retinal breaks. Patients and Methods This is a single-center, retrospective, consecutive review of all RRDs with inferior retinal breaks that were treated with PPV and segmental SB without an encircling band between May 2019 and February 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Vitrectomy is preferred in cases with complicating factors at the time of presentation, and in eyes with pseudophakic detachment, multiple or posterior retinal breaks, and vitreous opacities. Additionally, multiple studies have demonstrated that the two procedures can be combined to produce superior results in cases of anterior or inferior tears [ 7 , 8 ]. These procedures and their combined approach have been explained in detail in recent reviews by Warren et al [ 9 ] and Sultan et al [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vitrectomy is preferred in cases with complicating factors at the time of presentation, and in eyes with pseudophakic detachment, multiple or posterior retinal breaks, and vitreous opacities. Additionally, multiple studies have demonstrated that the two procedures can be combined to produce superior results in cases of anterior or inferior tears [ 7 , 8 ]. These procedures and their combined approach have been explained in detail in recent reviews by Warren et al [ 9 ] and Sultan et al [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, similar to recent reports, inferior retinal detachments were associated with worse anatomical outcomes than non-inferior detachments. Inferior retinal detachments mostly carry a greater risk of recurrence, which may be related to the lack of silicone oil tamponade to the inferior retina, challenging patients posturing, high risk of PVR presence, and missed breaks in the case of vitreous hemorrhage 9 . Heussen et al found that inferior retinal detachments with breaks below 4 and 8 o'clock were more prone to SB surgery failure 10 .…”
Section: Resultsmentioning
confidence: 99%